Poland: State Aid in the Shadow of Retail Sales Tax - Mikos-Sitek, Agnieszka (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
The issue of admissibility of state aid and the rules of its application by Member States of the European Union has become, in recent years, an issue of particular importance in preventing distortion of competition in the internal market, especially in the context of the COVID-19 pandemic and the ongoing economic crisis. Regulating this issue has proved inadequate both at the level of the EU and at the level of national legislation, thus requiring analyses under new conditions and considering completely different needs of practice. The need to mitigate the negative effects of the economic crisis and to cater to a greater demand for various forms of public support, individual states demonstrated considerable legislative activity in this area and applied various solutions. In Poland, differentiated measures of state aid provided for in the scope of individual sections of the Temporary Framework were used in practice considering the size of the economic activity and its specificity. Although Poland encountered some problems in the performance of tasks in this area under the conditions of the COVID-19 pandemic, for example, in interpreting provisions concerning fundamental issues in the application of the Temporary Framework and EU regulations, it should be noted that both in terms of the amounts allocated to public aid, the number of its beneficiaries, and the variety of solutions and benefits introduced, the activity of the state, also in terms of notifying the European Commission of its own aid programmes, was significant. Keywords: state aid, aid programme, entrepreneur, competition rules, internal market